Geographic range, spread and potential distribution of the painted reed frog Hyperolius marmoratus in the Western Cape Province, South Africa - Davies, Sarah J. (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2014.